PEMBELAJARAN DENGAN METODE BERCAKAP-CAKAP DI MASA PANDEMI MENGGUNAKAN MEDIA GAMBAR BERVARIASI PADA KELOMPOK B TK AN-NUR MULIA - Mulyati Mulyati; Lily Yuntina (Jurnal CARE (Children Advisory Research and Education), 2022)
The purpose of this study was to find out and obtain information about the learning outcomes of students' language skills using the conversational method using Varied Picture Media in Group B of An-nur Mulia Kindergarten Gunungsindur, Bogor District, for the 2019/2020 school year.Approach to qualitative research, the type of classroom action research, the action model from Kemmis Taggart which consists of Pre-cycle, Cycle I and Cycle II. Each Cycle consists of Planning, Implementation, Observation and Reflection Activities, data collection techniques in the form of interviews, observations and documentation. The population of this study were all students of PAUD An-Nur Mulia. The research subjects were in a group of 12 students. The results of classroom action research on pre-cycle activities were only 42% of the student categories began to develop in the first cycle of 68% developing as expected and after doing the second cycle there was an increase to 81% developing very well.Keywords: Early Childhood Learning, Conversation Method, Varied Picture Media